Sintering effect on mechanical properties of composites of enamel derived hydroxyapatite (EHA) and titanium - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2006)
Hydroxyapatite (HA) is one of the most promising biomaterials, which is on use since decades in biomedicine. Because of the known mechanical weakness of HA in load carrying situations, various dopants, like ceramic oxides and metallic particles, have been used to produce HA-composite materials. In this study, Ti powders were admixed with enamel derived HA at 5 and 10 wt %. After ball milling, the mixtures were uniaxially pressed into pellets of a cylindrical form. The composites were sintered at temperatures between 1000 degrees C and 1300 degrees C. Microhardness, compression strength, and density measurements together with X-ray diffraction analysis and SEM studies were performed. The best mechanical values were obtained for the samples sintered between 1100 degrees C and 1300 degrees C.
Keywords: enamel derived hydroxyapatite; titanium; sintering; mechanical properties